Global social work : crossing borders, blurring boundaries - Noble, Carolyn; Strauss, Helle; Littlechild, Brian, 1953- (The University Of Sydney, Australia : Sydney University Press, 2014)
Global Social Work: Crossing Borders, Blurring Boundaries provides a reference point for moving the current social work discourse towards understanding the local and global context in its broader significance.
Includes bibliographical references.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Social service -- International cooperation; Social work education; Human services -- International cooperation; Electronic books